2021
DOI: 10.6004/jnccn.2020.7646
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Characteristics Associated With Short Hospice Length of Stay for Patients With Solid Tumors Enrolled in Phase I Clinical Trials

Abstract: Background: Patients participating in phase I trials represent a population with advanced cancer and symptoms, with quality-of-life implications arising from both disease and treatment. Transitions to end-of-life care for these patients have received little attention. Good empirical data are needed to better understand the role of advance care planning and palliative care during phase I trial transitions. We investigated how physician–patient communication at the time of disease progression, patient characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[2][3][4]65,66 Phase I cancer clinical trial participants may struggle to cope with the uncertainty regarding their future and the many symptoms associated with their cancer and prior treatment. [5][6][7][8]32,[67][68][69] Participants are at risk for many symptom concerns, 1,9,10,64,70,71 with a symptom burden that may include fatigue, sleep disturbance, nausea, decreased appetite, anxiety, pain, and bowel changes. 7,11,12,62,68,72 Investigators recently reported (note: study not from the systematic review) patient-reported outcomes with many symptoms, including bloating, constipation, frequent urination, dry mouth, shortness of breath, anxiety, depression, and problems with memory and concentration affecting nearly 40% of the patients that they rated as severe or very severe.…”
Section: Clinical Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4]65,66 Phase I cancer clinical trial participants may struggle to cope with the uncertainty regarding their future and the many symptoms associated with their cancer and prior treatment. [5][6][7][8]32,[67][68][69] Participants are at risk for many symptom concerns, 1,9,10,64,70,71 with a symptom burden that may include fatigue, sleep disturbance, nausea, decreased appetite, anxiety, pain, and bowel changes. 7,11,12,62,68,72 Investigators recently reported (note: study not from the systematic review) patient-reported outcomes with many symptoms, including bloating, constipation, frequent urination, dry mouth, shortness of breath, anxiety, depression, and problems with memory and concentration affecting nearly 40% of the patients that they rated as severe or very severe.…”
Section: Clinical Interpretationmentioning
confidence: 99%
“…Study authors have also reported findings that few phase I clinical trial participants complete advance care planning and/or receive palliative care or hospice care at the end of life. 5,8,32,69,73 In a recent study of phase I clinical trial participants, only 39% completed an advanced directive, 35% had a designated health care proxy, and 37% enrolled in hospice despite a 10.1-month median survival from enrollment. 5 Another study demonstrated that 47% had received a palliative care consult, and only 53% had a documented goals-of-care discussion.…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations